Material–temporal registers of belonging: Theorising the interplay between temporality and the built environment. (February 2020) - Lewis, Camilla; May, Vanessa
This paper explores the interplay of temporality and the built environment in diverging discourses of belonging at Claremont Court, a modernist housing scheme in Edinburgh which was designed in 1958 by Sir Basil Spence, a key figure of post-war architecture. It explores belonging to place as a complex temporal process, in which the individual is connected to the built environment through various material–temporal registers. While existing analyses of belonging demonstrate that it is a fundamentally temporal experience, not enough is known about belonging as a temporal phenomenon. To fill this gap, our analysis reveals how multiple temporalities of the built environment are entwined with residents' biographies, everyday life and future aspirations, which shape their varied sense of belonging. To conclude, we argue not only for theorising the temporal nature of belonging, but also how the temporality of the built environment shapes people's sense of belonging. In doing so, we extend the literature on belonging by theorising the relationship between temporality and the built environment with the help of the concept of material–temporal registers.